2010
DOI: 10.1111/j.1365-313x.2010.04319.x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted access of proteins to mannan polysaccharides in intact plant cell walls

Abstract: SUMMARYHow the diverse polysaccharides present in plant cell walls are assembled and interlinked into functional composites is not known in detail. Here, using two novel monoclonal antibodies and a carbohydrate-binding module directed against the mannan group of hemicellulose cell wall polysaccharides, we show that molecular recognition of mannan polysaccharides present in intact cell walls is severely restricted. In secondary cell walls, mannan esterification can prevent probe recognition of epitopes/ligands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(185 citation statements)
references
References 54 publications
(159 reference statements)
5
179
1
Order By: Relevance
“…As shown in Supplemental Figure S4, antibodies directed to the RG-I backbone, extensin, xylan, arabinan, and HG showed relatively strong binding to mucilage extracts, indicating the presence of these polymers in the mucilage. Other antibodies, including LM21 and CCRC-M170 directed to heteromannan (Marcus et al, 2010) and acetylated mannan (Zhang et al, 2014), respectively, showed very low binding to mucilage, confirming the low contents of these epitopes in mucilage. JIM5 and JIM7 can detect low methylesterified HG and high methylesterified HG (Clausen et al, 2003), respectively.…”
Section: The Biochemical Properties Of Nonmannan Polysaccharides Arementioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Supplemental Figure S4, antibodies directed to the RG-I backbone, extensin, xylan, arabinan, and HG showed relatively strong binding to mucilage extracts, indicating the presence of these polymers in the mucilage. Other antibodies, including LM21 and CCRC-M170 directed to heteromannan (Marcus et al, 2010) and acetylated mannan (Zhang et al, 2014), respectively, showed very low binding to mucilage, confirming the low contents of these epitopes in mucilage. JIM5 and JIM7 can detect low methylesterified HG and high methylesterified HG (Clausen et al, 2003), respectively.…”
Section: The Biochemical Properties Of Nonmannan Polysaccharides Arementioning
confidence: 90%
“…6, D and J). The LM21 antibody, which recognizes heteromannan specifically (Marcus et al, 2010), labeled adherent mucilage in a similar manner as Calcofluor White. The LM21 immunolabeling results between wild-type and csla2-1 seeds were similar to the Calcofluor White results (Fig.…”
Section: The Biochemical Properties Of Nonmannan Polysaccharides Arementioning
confidence: 99%
“…In this study, mannan was detected with the LM21 and LM22 monoclonal antibodies, which are known to bind to mannan, glucomannan, legume seed galactomannan, and mannan/glucomannan (Marcus et al, 2010). Both LM21 and LM22 bound in an equivalent manner to three samples of galactoglucomannan obtained from pine wood (data not shown).…”
Section: Immunolocalization Of Cell Wall Polysaccharides In Normal Anmentioning
confidence: 99%
“…Polysaccharides were examined by ELISA analysis as described by Marcus et al (2010) to confirm binding of LM21 and LM22 to pine mannan.…”
Section: Determination Of Binding To Pine Galactoglucommananmentioning
confidence: 99%
“…6B). The PL buffer (pH 10) was included because the high pH has been demonstrated previously to degrade pectin backbones that break down under basic conditions (50). Moreover, arabinan can contain various esters (e.g.…”
Section: Ecp Interaction With Spinach Arabinosyl Residues In Pectin-mentioning
confidence: 99%